2015
DOI: 10.1016/j.pharep.2015.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Tideglusib protects neural stem cells against NMDA receptor overactivation

Abstract: Our study provides the evidence that GSK-3β and PPARγ may be directly involved in pathways leading to NMDA receptor-induced cell death and that the inhibitors including tideglusib may exert neuroprotective effect against these receptor overactivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Interestingly, pretreatment with 2.5μM tideglusib for 1 h significantly reduced LDH leakage due to NMDA. [68]. Moreover, a mechanistic study of tideglusib on Human African trypanosomiasis (HAT) reported a significant non-reversible, time-dependent inhibition of GSK-3 leading to significant inhibition of parasitic growth [69].…”
Section: Tideglusibmentioning
confidence: 99%
“…Interestingly, pretreatment with 2.5μM tideglusib for 1 h significantly reduced LDH leakage due to NMDA. [68]. Moreover, a mechanistic study of tideglusib on Human African trypanosomiasis (HAT) reported a significant non-reversible, time-dependent inhibition of GSK-3 leading to significant inhibition of parasitic growth [69].…”
Section: Tideglusibmentioning
confidence: 99%
“…), two thiadiazolidinones that had been previously reported by the same research team . This compound, later named tideglusib, is an irreversible, non‐ATP‐competitive GSK‐3β inhibitor with IC 50 values in the nanomolar range, and was also found to protect neural stem cells against the overactivation of NMDA receptors that lead to neuronal excitotoxicity . In transgenic mice overexpressing human mutant AβPP and tau protein, tideglusib was able to prevent hippocampal neuronal cell death and associated memory loss, while promoting a decrease in the levels of phosphorylated tau and a reduction in brain beta‐amyloid burden .…”
Section: Rational Design and Synthesis Of Novel Molecular Entities Tamentioning
confidence: 94%
“…Troglitazone was approved in 1997, but it was withdrawn from the market for increased risk of liver failure and extensive hepatotoxicity in 2000 (Kohlroser et al 2000). Tideglusib is a potent, irreversible, non ATP-competitive glycogen synthase kinase-3β (GSK-3β) inhibitor and PPARγ agonist tideglusib seems to be suitable candidate for Alzheimer disease treatment or for a treatment of stroke (Armagan et al 2015), but its application in cardiovascular disease treatment has not been examined yet.…”
Section: Pparγ and The Pi3k/akt/enos Signaling Pathwaymentioning
confidence: 99%